Associations Between Relapses and Psychosocial Outcomes in Patients With Schizophrenia in Real-World Settings in the United States - Lin, Dee; Joshi, Kruti; Keenan, Alexander; Shepherd, Jason; Bailey, Hollie; Berry, Mia; Wright, Jack; Meakin, Sophie; Benson, Carmela; Kim, Edward (Frontiers in Psychiatry, 2021)
Aim: To assess the association between relapses and psychosocial outcomes in adult patients with schizophrenia treated in United States (US) healthcare settings. Methods: Data were derived from a point-in-time survey of psychiatrists and their patients with schizophrenia conducted across the US, France, Spain, China and Japan between July and October 2019 For the purposes of this analysis only data from US practitioners was included. Disease specific programmes (DSPs) are large surveys with a validated methodology conducted in clinical practice; they describe current disease management, disease-burden impact, and associated treatment effects (clinical and physician-perceived). Participating psychiatrists completed patient record forms for their next 10 consecutive adult consulting patients with schizophrenia, with the same patients invited to voluntarily complete a patient self-completion (PSC) questionnaire. Surveys contained questions on the patients’ disease background, treatment history, prior hospitalisation due to schizophrenia relapse and a series of psychosocial outcomes. The association between relapses in the last 12 months and psychosocial outcomes were examined using multiple regression. Results: A total of 124 psychiatrists provided data on 1204 patients. Of these, 469 patients (mean age, 39.6 years; 56.5% male) had known hospitalisation history for the last 12 months and completed a PSC; 116 (24.7%) patients had ≥1 relapse. Compared to patients without relapses, patients who relapsed were more likely to be homeless, unemployed, previously incarcerated, and currently have difficulties living independently (all p<.05). Patients who experience a relapse also had greater working impairment and poorer quality of life compared with those who did not relapse. In general, psychosocial outcomes became poorer with an increasing number of relapses. Conclusions: In this population of patients with schizophrenia from the US, relapse was significantly associated with poor psychosocial outcomes, with a greater number of relapses predicting worse outcomes.. Early intervention to reduce the risk of relapse may improve psychosocial outcomes in patients with schizophrenia.